2008
DOI: 10.1021/jp709730b
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Tuning in Visual Pigments: An ONIOM(QM:MM) Study on Bovine Rhodopsin and its Mutants

Abstract: We have investigated geometries and excitation energies of bovine rhodopsin and some of its mutants by hybrid quantum mechanical/molecular mechanical (QM/MM) calculations in ONIOM scheme, employing B3LYP and BLYP density functionals as well as DFTB method for the QM part and AMBER force field for the MM part. QM/MM geometries of the protonated Schiff-base 11-cisretinal with B3LYP and DFTB are very similar to each other. TD-B3LYP/MM excitation energy calculations reproduce the experimental absorption maximum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
194
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(212 citation statements)
references
References 82 publications
18
194
0
Order By: Relevance
“…As also observed in hMeOp and sqRh, nonpolar amino acids are mainly located around the β-ionone ring. In line with previous results (40)(41)(42)), the Rh model shows that the largest electrostatic effect is due to the putative E113 counterion (SI Appendix, Fig. S6).…”
Section: Significancesupporting
confidence: 91%
“…As also observed in hMeOp and sqRh, nonpolar amino acids are mainly located around the β-ionone ring. In line with previous results (40)(41)(42)), the Rh model shows that the largest electrostatic effect is due to the putative E113 counterion (SI Appendix, Fig. S6).…”
Section: Significancesupporting
confidence: 91%
“…It should be noted that the absolute max s calculated by using this method often deviate from the comparable experimental values, but the max -shifts generally match with the experimental values (24). Here, the visual pigments with unprotonated and protonated SBRs have max s of 391-417 and 441-463 nm, respectively, which are significantly higher than the comparable experimental values (Table 1).…”
Section: Resultssupporting
confidence: 58%
“…The geometries were optimized at pure AMBER96 force field level (http://ambermd.org) after including H atoms and were further refined by hybrid quantum mechanical/molecular mechanical (QM/MM) calculations in the ONIOM (Our own N-layer Integrated molecular Orbital ϩ molecular Mechanics) electronic embedding scheme (QM ϭ B3LYP; MM ϭ AMBER) (24). The QM portion consists of the 11-cis-retinal, Schiff-base N-H moiety, and Glu-113 along with hydrogen link atoms.…”
Section: Oniom (Qm/mm) Analyses Of Lampfish and Its Mutantmentioning
confidence: 99%
See 1 more Smart Citation
“…QM/MM approaches have been successfully applied to to the modelling of chromophores in complex environments, such as pigments in pigment-protein complexes [3][4][5]. However, recent work has shown that a range of properties of interest of systems embedded in complex environments, including the absorption properties of small solvated dyes, require the explicit inclusion of large parts of the embedding environment into the QM region in order to obtain consistently converged results [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%